2017
DOI: 10.1002/hup.2584
|View full text |Cite
|
Sign up to set email alerts
|

L-carnosine as an adjuvant to fluvoxamine in treatment of obsessive compulsive disorder: A randomized double-blind study

Abstract: L-carnosine results in significant reduction of obsessive-compulsive symptoms when used as an adjuvant to fluvoxamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…Different placebo-controlled studies showed some effectiveness in refractory OCD of add-on treatments with mavoglurat [265], eicosapentaenoic acid [266], celecoxib [267], L-carnosine [268], inositol [269], the 5-HT 3 antagonist granisetron [270], the µ-opioid agonist morphine [228], and the β-adrenoceptor/5-HT 1A antagonist pindolol [271].…”
Section: Other Medicationsmentioning
confidence: 99%
“…Different placebo-controlled studies showed some effectiveness in refractory OCD of add-on treatments with mavoglurat [265], eicosapentaenoic acid [266], celecoxib [267], L-carnosine [268], inositol [269], the 5-HT 3 antagonist granisetron [270], the µ-opioid agonist morphine [228], and the β-adrenoceptor/5-HT 1A antagonist pindolol [271].…”
Section: Other Medicationsmentioning
confidence: 99%
“…45 Rodriguez et al reported that ketamine infusion, a non-competitive NMDA glutamate receptor antagonist, without the use of an SRI, can cause reduction in OCD symptoms. 46 Possible effect of lamotrigine, 47 topiramate, 48 L-carnosine, 49 and Week Y-BOCS Obsession score 10 12 minocycline 7 in reduction of OCD symptoms has been shown in similar studies. Amantadine is an uncompetitive antagonist of NMDA-type glutamate receptor that has a neuroprotective potential.…”
Section: Discussionmentioning
confidence: 60%
“…reported that ketamine infusion, a non‐competitive NMDA glutamate receptor antagonist, without the use of an SRI, can cause reduction in OCD symptoms . Possible effect of lamotrigine, topiramate, L‐carnosine, and minocycline 7 in reduction of OCD symptoms has been shown in similar studies.…”
Section: Discussionmentioning
confidence: 66%
“…51 On the other hand, L-carnosine has been less investigated for OCD, but the only available controlled trial (1 g of L-carnosine as add on to fluvoxamine) showed good results. 55,56 Lamotrigine and Topiramate Lamotrigine and topiramate are two inhibitors of the glutamate AMPA (alpha-amino-3-hydroxy-5-methyl-4-isoxazole-propionate) receptors. 57 Lamotrigine showed a significant effect on OCD symptoms in two different placebo-controlled trials as add-on to SRIs.…”
Section: N-acetylcysteine (Nac) and L-carnosinementioning
confidence: 99%